Interrater Reliability dan Internal Consistency Pengkajian Luka Kaki Diabetik The New Diabetic Foot Ulcer Assessment Scale (DFUAS) Berbasis Foto - Nurawaliah Rasyid; Saldy Yusuf; Takdir Tahir (Politeknik Kesehatan Kemenkes Mamuju, 2019)
Diabetic foot ulcers have a high prevalence that requires good management of care. One of them is by assessing diabetic foot wounds. Currently, there has been a review of diabetic foot healing footage of New Diabetic Foot Ulcer Assessment Scale (DFUAS) which has been tested for validity and photo-based reliability. Nevertheless, in the DFUAS Assessment Reliability Test, there are still differences in perceptions on several DFUAS assessment variables on wound nurses. One reason is that there is no socialization given to the wound nurses on how to assess the DFUAS assessment. In addition, the previous DFUAS assessment reliability test is only performed on certified wound nurses whereas in health care services in patients with diabetic foot injuries are also performed by non-certified general nurses. This study aims to assess the interrater reliability and internal consistency of DFUAS-based on photo assessment on expert nurses and general nurses. The design of this study was cross sectional study. The samples in this study were certified nurses with ETN, CWCC, CWCCA and general non-certified Nurses with more than 2 years experience of wound care. The nurse as an observer evaluated 8 wounded images divided according to the wound stage (necrotic, slough, granulation and epithelial) using DFUAS assessment. Interrater reliability was assessed by spearman rho while internal consistency was assessed by cronbach's alpha. Interrater reliability shows good correlation with spearman rho> 0.60. Internal consistency shows good reliability between DFUAS assessment items and Cronbach's alpha 0.98. This study shows that the DFUAS assessment is reliable on different nurses both certified nurses and general nurses.